Event marketing ve společnosti Škoda Auto, a.s. - Kroulíková, Daniela; Kroulíková Daniela (České vysoké učení technické v Praze, 2017)
Bakalářská práce na téma "Event marketing a jeho využití ve společnosti Škoda Auto, a. s." se zaměřuje na event marketing jako účinný komunikační marketingový nástroj. Smyslem mé práce je správné začlenění tohoto nástroje do komunikačního mixu společnosti. Cílem celé práce je porovnání teoretických i praktických hledisek event marketingu a jejích následné zmapování při pořádání akcí YETI PARK a KODIAQ CAMP. V závěru práce provedu zhodnocení obou eventů a možná zlepšení v celkové oblasti chápání event marketingu vozů společnosti Škoda Auto, a. s. do budoucna.

The Bachelor's thesis "Event marketing and its usage in the company Škoda Auto, a.s." is focused on event marketing as an effective marketing tool. The aim of this work is an appropriate implementation of this tool in the communicative mix of the company. The thesis discusses a comparison of both theoretical and practical aspects of event marketing and their mapping throughout the organization of the "YETI PARK" and "KODIAQ CAMP" events. An evaluation of said events and a discussion of proposals, with a focus on a future general understan- ding of event marketing of the Škoda Auto, a.s. cars are carried out at the end of the thesis.
Event marketing in the Company Škoda Auto, a.s.
Keywords: event marketing,strategie,cílová skupina,komunikační mix; event marketing,strategy,target group,communication mix